2017
DOI: 10.1016/j.biortech.2017.04.093
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus batch production of lipids in the microalgae Acutodesmus obliquus

Abstract: This work provides a novel quantitative comparison of batch versus continuous microalgal lipid production in the wild type and starchless mutant strain of Acutodesmus obliquus. Both strains showed higher TAG yields on light under batch operation compared to continuous nitrogen limitation. The starchless mutant showed 0.20gTAGmol for batch and 0.12gTAGmol for continuous operation, while the wildtype only showed 0.16gTAGmol for batch and 0.08gTAGmol for continuous operation. Also, higher TAG contents were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 48 publications
4
52
0
Order By: Relevance
“…However, TAG productivity R TAG increased with increasing MRPA A XA when expressed per kg of active biomass X A indicating that TAG production rate was certainly limited by a reaction governed by light absorption. In this study, maximum TAG productivity reached 2.6 g/m 2 ⋅day for the culture featuring MRPA equal to 17,700 μmol hν /kg XA s. This is similar to maximum TAG productivity of 2.2 g/m 2 ⋅day reported by Remmers et al [10] for the wild type A. obliquus grown in continuous mode with a mean rate of photon absorption estimated to be 13,080 μmol hν /kg XA s. The latter was determined assuming a steady-state biomass and TAG concentrations of 2.45 kg/m 3 (with active biomass fraction 0.52) and 22.1 dry wt%, respectively, and full absorption of the 333 μmol hv /m 2 ⋅s incident on the PBR. The similarity of both maximum TAG productivity and its corresponding MRPA reported here and in Ref.…”
Section: Mean Specific Rate Of Photon Absorptionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, TAG productivity R TAG increased with increasing MRPA A XA when expressed per kg of active biomass X A indicating that TAG production rate was certainly limited by a reaction governed by light absorption. In this study, maximum TAG productivity reached 2.6 g/m 2 ⋅day for the culture featuring MRPA equal to 17,700 μmol hν /kg XA s. This is similar to maximum TAG productivity of 2.2 g/m 2 ⋅day reported by Remmers et al [10] for the wild type A. obliquus grown in continuous mode with a mean rate of photon absorption estimated to be 13,080 μmol hν /kg XA s. The latter was determined assuming a steady-state biomass and TAG concentrations of 2.45 kg/m 3 (with active biomass fraction 0.52) and 22.1 dry wt%, respectively, and full absorption of the 333 μmol hv /m 2 ⋅s incident on the PBR. The similarity of both maximum TAG productivity and its corresponding MRPA reported here and in Ref.…”
Section: Mean Specific Rate Of Photon Absorptionsupporting
confidence: 90%
“…The similarity of both maximum TAG productivity and its corresponding MRPA reported here and in Ref. [10] provides further confidence in the use of MRPA expressed per kg of active biomass to optimize TAG productivity in nitrogen limited cultures. Kandilian et al [32] previously demonstrated TAG productivity in nitrogen starved Nannochloropsis oculata and MRPA had a parabolic relation where maximum productivity occurred at 14 μmol hv /m 2 ⋅s.…”
Section: Mean Specific Rate Of Photon Absorptionsupporting
confidence: 79%
See 1 more Smart Citation
“…Due to the expanding biobased economy, the interest in microbial oil is increasing (Athenaki et al 2018;Sitepu et al 2014a, b). The possibility of economically feasible bio-oil production is being investigated in algae, yeasts, and filamentous fungi (Remmers et al 2017;Hao et al 2016;Sitepu et al 2014b;Ageitos et al 2011). However, an economically viable production process will require improvements to oil yield through optimization of cultivation and processing, as well as isolation of multiple coproducts in a biorefinery setup, indicating the need for mild downstream processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…14 Acutodesmus obliquus (Scenedesmus obliquus UTEX 393) was chosen for this research due to its biomass potential for biodiesel production as well as its greater potential for use as lipid producer, all these attributes being due to its tolerance to pH variation and easy culturing when nitrogen starvation (stress phase) is involved. 15,16 www.soci.org DX Hurtado et al…”
Section: Introductionmentioning
confidence: 99%